Injectable poly(organophosphazene) hydrogel system for effective paclitaxel and doxorubicin combination therapy. (September 2014) - Cho, Jung-Kyo; Kuh, Hyo-Jeong; Song, Soo-Chang
Abstract Combination therapy is an important option for gastric cancer which is the second leading cause of cancer-related death worldwide. The administration schedule of cell cycle-specific drugs, such as doxorubicin (DOX) and paclitaxel (PTX), is important for therapeutic efficacy. However, to control the schedule is clinically inconvenient. Additionally, in vitro cytotoxicity tests against human gastric cancer cells (SNU-601) showed that the combination indices (CIs) of DOX and PTX were 1.43 (α = 0) and 1.90 (α = 1), respectively, indicating that the DOX and PTX interaction was antagonistic. Thus, based on the finding that the release rate of drugs from poly(organophosphazene) (PPZ) hydrogel is dependent on the hydrophobicity of the drugs, we used injectable PPZ hydrogel in combination therapy. In vivo anticancer activity test in human gastric cancer cell-xenografted mice showed that intratumoral injection with aqueous PPZ solution, containing DOX (15 mg/kg) and PTX (30 mg/kg), resulted in the highest tumor inhibition and safety (no mortality for approximately 3 months) in the experimental groups. Consequently, PPZ hydrogel is expected to be a promising drug delivery system for cell cycle-specific drugs, facilitating the control of their administration schedule for effective combination therapy.